The Lingering Conflict : Israel, the Arabs, and the Middle East 1948-2012. - Rabinovich, Itamar (Brookings Institution Press, 2012)
In The Lingering Conflict Itamar Rabinovich, a former chief negotiator for Israel, providesunique and authoritative insight into the prospects for genuine peace in the Middle East. His presentation includes a detailed insider account of the peace processes of 1992-96 and a frank dissection of the more dispiriting record since then. Rabinovich's firsthand experiences as a negotiator and as Israel's ambassador to the United States provide a valuable perspective from which to view the major players involved. Fresh analysis of ongoing situations in the region and the author'sautho.